Hyperglycemia promotes SIRT3-mediated deacetylation of SARM1 to exacerbate diabetic peripheral neuropathy in mice - Chunyu Chen; Liliang Zhu; Wenxi Li; Yuefeng Jiang; Zhe Zhang; Yongjuan Zhao; Jinzhong Lin; Wei Yu (Proceedings of the National Academy of Sciences, 2026)
Diabetic peripheral neuropathy (DPN), the most common complication of diabetes, lacks effective treatments and is characterized by early axonal degeneration mediated by sterile alpha and Toll/interleukin receptor motif-containing protein 1 (SARM1). Here, we identify a regulatory mechanism of SARM1’s NAD + -cleaving activity via acetylation at lysine 641 (K641). In high-glucose conditions, SIRT3 deacetylates SARM1 at K641, enhancing its NAD + cleavage activity and exacerbating axonal damage. In type 2 diabetic (T2DM) mice, acetylation of SARM1 at K641 (K641Ac) or Sirt3 knockout mitigates hypoalgesia, intraepidermal nerve fiber loss in footpad skin, and axonal growth retardation in dorsal root ganglia. These interventions also attenuate ROS accumulation, ATP depletion, and NAD + decline, conferring protection against DPN pathology. Notably, wild-type SARM1 expression reverses the protective effects of Sirt3 ablation in T2DM mice, whereas SARM1 K641Q does not. Our findings establish that SIRT3-mediated deacetylation of SARM1 at K641 drives axonal degeneration in DPN, and enhancing K641 acetylation mitigates disease progression. This study uncovers a critical posttranslational regulation of SARM1 and suggests that targeting the SIRT3–SARM1 axis may offer therapeutic potential for DPN and related neurodegenerative conditions.